Projective Identification, Concretely Experienced: A Preliminary Daseinsanalytic Reformulation (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
The author appropriates Boss's (1963/1979) Daseinsanalytic theory to reformulate the directly observable interpersonal experiences frequently explained (and obscured) by the object relational concept of projective identification. Projective identification can be understood in a more experience-near manner, giving them a much greater measure of scientific credibility and emotional resonance.
Keywords: Daseinsanalysis; Medard Boss; psychoanalysis; object relations; projective identification; psychotherapy